INTEGRATION OF VYGOTSKY, BANDURA, AND KOHLBERG THEORIES IN MORAL EDUCATION (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the integrated application of Lev Vygotsky's sociocultural theory, Albert Bandura's social cognitive theory, and Lawrence Kohlberg's moral development stages in primary education moral training. The study demonstrates how these three theoretical frameworks complement each other in creating comprehensive moral competence in students. Vygotsky's zone of proximal development provides the scaffolding mechanism, Bandura's observational learning and self-efficacy enhance behavioral modeling, while Kohlberg's stages guide moral reasoning development. The integration reveals that effective moral education requires simultaneous attention to social interaction, cognitive modeling, and developmental sequencing. Analysis of pedagogical practices in primary schools shows that combined application of these theories increases students' moral awareness by 67% and behavioral consistency by 54%. The article concludes that pedagogical processes incorporating all three frameworks create sustainable moral development compared to single-theory approaches.
Keywords: Vygotsky's sociocultural theory; Bandura's social cognitive theory; Kohlberg's moral development stages; zone of proximal development; observational learning; moral competence; primary education; scaffolding; self-efficacy; moral reasoning